CREATIVE KPI MODEL: A BEHAVIORAL APPROACH TO EVALUATING THE PERFORMANCE OF VISUAL COMMUNICATION DESIGNERS - Ferry Eldeni T; Gogi Kurniawan; Dani Rohmati; Hafidulloh (Yayasan Nuraini Ibrahim Mandiri, 2025)
This study aims to identify the work behavior patterns of visual communication designers and to develop appropriate Key Performance Indicators ( KPIs ) to support People Management at Ruang Creative Surabaya. Employing a qualitative approach with a case study design , data were collected through interviews , observations , and document analysis , then validated using triangulation and analyzed via thematic analysis . The study identified six main dimensions of work behavior : quality of work , timeliness , initiative , cooperation , personal qualities , and creativity . These dimensions were formulated into a KPI framework with proportional weighting , where quality of work (25%) and timeliness (20%) are prioritized , while the other dimensions complement qualitative aspects reflecting creativity , collaboration , and integrity . This research contributes in three ways : theoretically , by expanding performance management studies through the integration of behavior and creativity ; practically , by providing an evaluation framework that balances organizational discipline with artistic freedom ; and contextually , by enriching Indonesian creativity industry literature with empirical evidence from a local design agency